DIPLOMASI PUBLIK KOREA SELATAN DI INDONESIA MELALUI SEKTOR PENDIDIKAN KOREA INTERNATIONAL COOPERATION AGENCY (KOICA) - Jayanti, Ajeng Dwi; Suwartiningsih, Sri; Ismoyo, Petsy Jessy (Universitas Kristen Satya Wacana, 2019)
Public diplomacy is currently the most frequent diplomacy by many countries in the world. South Korea is one country that uses Public Diplomacy to achieve its interests. Public diplomacy conducted by South Korea is not only happening through the field of cultural art alone, public diplomacy is also done by South Korea in the field of education. Through the education sector of Korea International Cooperation Agency (KOICA), South Korea is helping developing countries to advance education in their country. The purpose of this study is to explain South Korea's public diplomacy in Indonesia through the Korea International Cooperation Agency (KOICA) education sector. This topic, analyzed with the concept of Public Diplomacy, Soft Power and Constructivist theory. This research uses qualitative approach through data analysis technique. Researchers used literature searches related to the topics that researchers covered. An important conclusion is that the education sector has an objective strategy in its efforts to help improve education in Indonesia, namely Quality Primary Education, Training Technical Resources and Development of Human Resource through Higher Education. Projects implemented in Indonesia conform to the main objectives of KOICA's education sector, to provide quality basic education, training of technical resources and other resources through higher education, and to facilitate educational opportunities and improve the quality of education, education policies and systems From partner countries.